Environmental Assessment of heavy metals Concentration and Distribution in Surface Soils of Wasit Governorate/ Iraq - Muslim, Ruaa Issa; Issa, Murtadha J.; AL-Obaidi, Basim Shaker (Iraqi Journal of Science, 2019)
Wasit Governorate is characterized by industrials activities such as groups of asphalts and bricks factories, oil fields and thermal power plant, in addition to the agricultural activity that is widely separated, which leads to pollution of the surface soils with heavy metals. The main objective in this research is to assess heavy metals pollution and understand the distribution in the surface soils in the studied area. Twenty two surface soils samples were collected from 6 districts and 4 subdistricts within Wasit Governorate during April 2017. The results obtained showed that grain size analyzes are classified as sandy mud (sand 9.5%, silt 50.8 % and clays 39.8%). In the term of geochemical parameters, high level of soil salinity in Wasit Governorate was in Badrah station (8%). Organic matter records 3.7% as a relative maximum concentration in industrial soils at 7.2 pH. Heavy metals Mo, Cu, Pb, Zn, Ni, Co, Mn, As, Cd,V, Cr, Br, Ta, Zr, Ba and Sr were investigated in the soils samples in Wasit Governorate. Assessment of heavy metal pollution has calculated by using the index of geo-accumulation (I-geo), Contamination factor (CF), pollution load index (PLI) and I-geo has been commonly applied as a degree of pollution in soils samples. The pollution load index (PLI) characterizes the number of times in which the heavy metal concentrations of sediment exceeds the background concentration; it provides a cumulative indication of the overall level of heavy metal toxicity in a certain sample. By using these statistical indexes of soils, the results show that soils samples in the studied area are very polluted by the heavy metals of Titanium (72.7 ppm), Nickel (188.9) to considerable with Molybdenum (9.85 ppm), Chromium (226 ppm), Cadmium (2.2ppm), bromine (27.ppm) and Strontium (431.6 ppm), and with moderate pollution of the heavy metals of Copper (54.7) Cobalt (13.4 ppm), Manganese (781.8ppm), Vanadium (104.3ppm) and zinc (117.6ppm